2008
DOI: 10.1042/ba20070140
|View full text |Cite
|
Sign up to set email alerts
|

New properties of inclusion bodies with implications for biotechnology

Abstract: Human G-CSF (granulocyte colony-stimulating factor) is a well-known biopharmaceutical drug being mostly produced by overexpression in Escherichia coli, where it appears in the form of IBs (inclusion bodies). Following our initial findings that properties of inclusion bodies strongly depend on the growth conditions used, especially growth temperature, we compared the characteristics of the G-CSF inclusion bodies prepared at two different temperatures, namely 42 and 25 degrees C. IBs formed at higher growth temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 32 publications
2
65
0
1
Order By: Relevance
“…Attempts to solubilize AtCESA1CatD under denaturing conditions using urea or lithium dodecyl sulfate were unsuccessful, resulting in protein aggregation during the refolding process. However, the protein was solubilized under non-denaturing conditions using a low concentration of sodium lauroyl sarcosine according to a previously reported protocol (García-Fruitós et al, 2005;Jevsevar et al, 2005;Peternel et al, 2008). The purified protein was .95% pure after size exclusion chromatography as judged by SDS-PAGE analysis (Fig.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…Attempts to solubilize AtCESA1CatD under denaturing conditions using urea or lithium dodecyl sulfate were unsuccessful, resulting in protein aggregation during the refolding process. However, the protein was solubilized under non-denaturing conditions using a low concentration of sodium lauroyl sarcosine according to a previously reported protocol (García-Fruitós et al, 2005;Jevsevar et al, 2005;Peternel et al, 2008). The purified protein was .95% pure after size exclusion chromatography as judged by SDS-PAGE analysis (Fig.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…It has been demonstrated that inside an IB there are heterologous and host proteins combining native-like structures with partially folded and misfolded proteins [13,[16][17][18][19][20][21]. The IB formation and its maintenance involve a complex network of intracellular responses related to culture conditions, leading to complex and stable structures sometimes showing bioactivity [13,22].…”
Section: Introductionmentioning
confidence: 99%
“…The IB formation and its maintenance involve a complex network of intracellular responses related to culture conditions, leading to complex and stable structures sometimes showing bioactivity [13,22]. Due to their different physicochemical properties, IBs have been proposed for various uses, such as catalysts, support materials, drug delivery agents, cell therapy, and immunogens, and their recent application has become an important new topic in biology, medicine and biotechnology [11,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these protein-based nanoparticles are mechanically stable (García-Fruitós et al, 2009), showing regulatable size (García-Fruitós et al, 2009), geometry (Garcia-Fruitos, Seras-Franzoso, Vazquez, & Villaverde, 2010, density (Peternel, Jevsevar, Bele, Gaberc-Porekar, & Menart, 2008), Z-potential, stiffness and wettability (Diez-Gil et al, 2010). Importantly, it is feasible to obtain IBs formed by almost any protein of interest, eventually assisted by pull-down peptides that act as fuzzy architectonic tags Garcia-Fruitos et al, 2005).…”
Section: Artificial Self-organizing Protein Constructs Inclusion Bodiesmentioning
confidence: 99%